Results of a Multicenter, Randomized, Double-Masked, Placebo-Controlled Clinical Study of the Efficacy and Safety of Visomitin Eye Drops in Patients with Dry Eye Syndrome. Issue 12 (December 2015) - Brzheskiy, Vladimir; Efimova, Elena; Vorontsova, Tatiana; Alekseev, Vladimir; Gusarevich, Olga; Shaidurova, Ksenia; Ryabtseva, Alla; Andryukhina, Olga; Kamenskikh, Tatiana; Sumarokova, Elena; Miljudin, Eugeny; Egorov, Eugeny; et al.
Abstract Introduction This article presents the results of an international, multicenter, randomized, double-masked, placebo-controlled clinical study of Visomitin (Mitotech LLC, Moscow, Russian Federation) eye drops in patients with dry eye syndrome (DES). Visomitin is the first registered (in Russia) drug with a mitochondria-targeted antioxidant (SkQ1) as the active ingredient. Methods In this multicenter (10 sites) study of 240 subjects with DES, study drug (Visomitin or placebo) was self-administered three times daily (TID) for 6 weeks, followed by a 6-week follow-up period. Seven in-office study visits occurred every 2 weeks during both the treatment and follow-up periods. Efficacy measures included Schirmer's test, tear break-up time, fluorescein staining, meniscus height, and visual acuity. Safety measures included adverse events, slit lamp biomicroscopy, tonometry, blood pressure, and heart rate. Tolerability was also evaluated. Results This clinical study showed the effectiveness of Visomitin eye drops in the treatment of signs and symptoms of DES compared with placebo. The study showed that a 6-week course of TID topical instillation of Visomitin significantly improved the functional state of the cornea; Visomitin increased tear film stability and reduced corneal damage. Significant reduction of dry eye symptoms (such as dryness, burning, grittiness, and blurred vision) was also observed. Conclusion Based on the results of this study, Visomitin is effective and safe for use in eye patients with DES for protection from corneal damage. Funding Mitotech LLC.